PALMPRINT CLASSIFICATION USING FIXED SIFT DESCRIPTORS NUMBER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
In this article we use, for palmprint feature extraction, descriptors generated with SIFT (Scale-invariant feature transform) algorithm. The main idea was to generate for each image in the dataset, the same number of keypoints. We deduced an algorithm that, for a given image, computes a fixed number of SIFT keypoints. The matching procedure is based on the nearest neighbor ratio equation. To test the efficacy of our method, we performed experiments on five well-known palmprint databases. The experimental results indicate that this type of approach yields very good classification results. Our results are better than those obtained in some recent papers.
Keywords: Scale-invariant feature transform keypoints; Keypoint matching; Palmprint classification